Clinical impact of pulmonary artery to aorta diameter ratio on left ventricular reverse remodeling in patients with dilated cardiomyopathy. (14th October 2021) - Shibata, N; Hiraiwa, H; Kazama, S; Kimura, Y; Araki, T; Mizutani, T; Oishi, H; Kuwayama, T; Kondo, T; Morimoto, R; Okumura, T; Murohara, T
Abstract: Background: Left ventricular reverse remodeling (LVRR) is an important predictor for a good prognosis in patients with dilated cardiomyopathy (DCM). Previous reports indicated the pulmonary artery diameter (PAD) to ascending aortic diameter (AoD) ratio as a predictor of adverse outcomes in heart failure patients. However, the impact of the PAD/AoD ratio for predicting LVRR in patients with DCM is unknown. Aim: The aim of this study is to investigate the association between PAD/AoD ratio and LVRR in patients with DCM. Methods: From a prospective study, clinically stable DCM patients who were investigated the LVRR on echocardiography and underwent CT at baseline were enrolled. LVRR is defined as left ventricular (LV) ejection fraction increase of 10% and a decrease in indexed LV end-diastolic diameter of 10% compared to those at baseline. PAD and AoD data was collected with nonenhanced computed tomography images at baseline. Results: In sixty-nine patients (mean age 50.0±13.3 years), the mean LV ejection fraction was 29.8%, and mean LV end-diastolic dimension was 64.5mm, and both of which data was no significant difference between patients with or without LVRR. LVRR was observed in 23 (33.3%) patients. The PAD/AoD ratio was significantly lower in patients with LVRR than without LVRR (81.4% vs. 92.4%, p=0.003). By ROC analysis, the best cut-off for the detection of LVRR was found for a PAD/AoD ratio of 0.9. From multivariate analyses, PAD/AoD ratio was identified as a significant predictor of LVRR. After a median follow-up duration of 2.5 years, the DCM patients with PAD/AoD≥0.9 revealed a significant higher cardiac event than those with PAD/AoD<0.9 (log-rank, p=0.007) Conclusions: The PAD/AoD ratio is useful for predicting LVRR in patients with DCM. The DCM patients with high PAD/AoD ratio had a poor long-term outcome. Funding Acknowledgement: Type of funding sources: None.